Sustainability Analysis of Nigeriaas Foreign Debt Profile and Management Strategies (Global Journal of Human-Social Science, 2016)
Over the years Nigeria has faced series of development challenges despite the fact that the governments have constantly accessed credit facilities for national development This contradiction became a source of worry for scholars journalists and commentators who began to question the management of the country s foreign debt The debate became more critical and controversial when Nigeria in attempt to wriggle itself out of the foreign debt burden negotiated Debt Relief with the major external creditors While some individuals share the view that the negotiated debt relief actually relieved Nigeria from its financial burden others contended that the purported Debt Relief more or less worsened Nigeria s indebtedness to the creditors because the conditions like previous ones associated with the debt management strategies were more exploitative than palliative Although attempts have been made to examine the country s debt management strategies by investigating the trends in Nigeria s debt profile adequate research-based attention has not been given to the extent which the Debt Relief is effective and sustainable Consequently this paper is tailored towards addressing the questions How effective were the debt management strategies adopted by the Nigerian government in addressing debt crisis Has the debt relief granted to Nigeria in 2006 actually relieved the country from the debt burden How sustainable is the debt relief This study is therefore meant to analyse Nigeria s foreign debt management and the challenges of sustainability In the light of the dependency theory and time-series analysis it is argued that Nigeria only enjoyed temporary relief from the debt crisis because the management strategies adopted so far were not effective as to ensure sustainability
Keywords: sustainability; foreign debt; debt profile; management strategies